La caducidad del ejercicio de revisión: el caso de las actuaciones previas y la autotutela. - Freire Carrillo, Verónica Marisol (2024)
The expiration of the exercise of review: The case of prior actions and self-protection is a critical topic, which must be approached reflexively and analytically from a doctrinal and legal study because the sanctioning and determining power that the public administration has, in the phase of prior actions, is limited to times that condition the public administration to clarify, rectify or correct the decision to initiate the previous action, or, in turn, to begin the administrative procedure, this before the expiration that could occur, either in two or six months respectively and on this, the possibility of once expired, to restart again the actions, before they expire. The following methods have been used as a study methodology: legal-historical, doctrinal, and legal-comparative, from a qualitative study, applying research tools such as interviews with specialists in the area, allowing me to achieve the objectives set. Concluding at a general level that, in the administrative procedures, if there is no cause or time of prescription, an administrative procedure can be initiated again for the exact cause of the original method, regardless of whether the expiration of the procedure has already been declared due to the causes of the self-protection of legality (revision of the law) or not.